Changing Chinese diets to achieve a win–win solution for health and the environment - Sheng, Fangfang; Wang, Jingjing; Chen, Kevin Z.; Fan, Shenggen; Gao, Haixiu (John Wiley & Sons, 2021)
Diets are key determinants of nutrition and health and play a significant role in the environment. In this article, we aim to (i) describe dietary transitions and health in China and the consequent environmental challenges; (ii) identify differences between current Chinese diets and healthy reference diets; (iii) conduct a systematic review assessing the health impacts of four reference diets on the Chinese population, and (iv) simulate changes in greenhouse gas emissions under different diet scenarios. The results show differences between the Chinese diets and reference diets, with the current Chinese diet including mainly grains (especially refined rice), excessive meat consumption, and insufficient consumption of fruit and milk. If all Chinese consumers adopt one of the healthy reference diets all the time, the incidence of diet‐related chronic disease and mortality would be significantly reduced. Such dietary shifts would also reduce greenhouse gas emissions by 146–202 million tons (18–25 percent) compared with the projected emissions level in 2030.